Dynamics of volcanic ash remobilisation by wind through the Patagonian steppe after the eruption of Cordón Caulle, 2011 - Panebianco, Juan Esteban (2017)
Wind erosion of freshly-deposited volcanic ash causes persistent storms, strongly affecting ecosystems and human activity. Wind erosion of the volcanic ash was measured up to 17 months after the ash deposition, at 7 sites located within the ash-deposition area. The mass flux was measured up to 1.5 m above ground level. Mass transport rates were over 125 times the soil wind-erosion rates observed before the ash deposition, reaching up to 6.3 kg m−1 day−1. Total mass transport of ash during the 17 months ranged between 113.6 and 969.9 kg m−1 depending on topographic location and wind exposure. The vertical distribution of the mass flux at sites with higher vegetation cover was generally inverted as compared to sites with lower vegetation cover. This situation lasted 7 months and then a shift towards a more uniform vertical distribution was observed, in coincidence with the beginning of the decline of the mass transport rates. Decay rates differed between sites. Despite changes over time, an inverse linear correlation between the mass transports and the mass-flux gradients was found. Both the mass-flux gradients and the average mass-transport rates were not linked with shear-stress partition parameters, but with the ratio: ash-fall thickness to total vegetation cover.